Improvement of extraction and stability of anthocyanins, the natural red pigment from roselle calyces using supercritical carbon dioxide extraction - Zuhaili, Idham; Nicky Rahmana, Putra; Ahmad Hazim, Abdul Aziz; Ahmad Syahmi, Zaini; Noor Azwani, Mohd Rasidek; Norlisa, Mili; Mohd Azizi, Che Yunus (Elsevier Ltd, 2022)
In this work, anthocyanins, a natural red pigment, were isolated from roselle calyces using supercritical carbon dioxide (SC-CO2). Three process conditions, namely pressure, temperature, and co-solvent ratio (ethanol-water), were investigated using a three-factorial design from response surface methodology (RSM). The method was used to model the extraction of anthocyanins, total phenolic content, total flavonoid content, and colour characteristics (i.e., lightness (L*), chroma (C*), and hue (h◦)). The best conditions were 27MPa, 58 ◦C, and 8.86 % cosolvent ratio at maximal anthocyanin, phenolic, and flavonoid content, with minimal L* and C* values. The anthocyanin production was 1197 mg/100 g of dried roselle calyces. Next, the high relative value of cyanidin 3- sambubioside and phenolic compound in SC-CO2 extract was analyzed using an ultra-high-performance liquid chromatogram (UHPLC). Anthocyanins stored at 4 ◦C, 25 ◦C, and 37 ◦C had average reaction rate (k) and half-life (t1/2) values of 0.0032 and 216 days, 0.0098 and 70 days, and 0.024 and 28 days for SC-CO2 and 0.0093 and 74 days, 0.0222 and 31 days, and 0.0444 and 15 days for solid-liquid extraction (SLE), respectively, in first-order degradation kinetics. These findings demonstrated that the studied conditions using SC-CO2 provided lower degradation rates and a longer t1/2 than the conventional SLE methods